ANALISIS KETERAMPILAN BERTANYA GURU ILMU PENGETAHUAN SOSIAL DI SMP NEGERI 27 OKU - Dini Indriyani; Yulia Djahir; Ikbal Barlian (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
This research was titled questioning skillsIPS’s teacherat SMPN 27 OKU. Formulation of the problem in this research is how are basic questioning skills and further questioning skills of IPS’s teacher at SMPN 27 OKU. The method used is descriptive. Variables in this researchare basic questioning skills and further questioning skills. Sample in this researchare 3 IPS’s teacherat SMPN 27 OKU. Data collection techniques used in this researchare observation and interviews. Result showed basic questioning skills on criteria very good with an average of 81,36% and further questioning skills on criteria good with an average of 58,93%. Deficiency of teachers in applying questioning skills seen in this researchare disclosure clearly questions with using Indonesian, alteration guidance cognitive level questions, and setting tracker question. As for suggestion of the research are that IPS’s teachercan better understand use questioning skills for successful learning in the classroom, designing the first questions to be asked during learning, and avoid habit to immediately respond to questions and answers learners.